Conflict and Its Discursive Representations: Sustaining Support for War - O'Connor, Ryan. author. aut Link
XIV, 382 p. 21 illus., 20 illus. in color.
Keywords: This project seeks to demonstrate how multiple sites of discursive production (political elite, media, and popular culture) interact to construct truths about a conflict that condition political possibility. Through breaking down the interaction between multiple sites of production within moments of discursive stability and by tracing major themes across multiple sites of discursive production this work will illuminate the processes by which the ‘truth’ for a conflict is produced, sustained, and challenged. Specifically, this project will be contesting two historical moments of ‘naturalness’ wherein a dominant discourse established a representational stability within American foreign policy in order to display how multiple sites of production work to produce, sustain, and challenge the political realities of military interventions. In doing so, the processes which impact the production of policy and public acceptance/condemnation for military interventions will be demonstrated. Ryan O’Connor is Senior Lecturer in Security Studies at Birmingham City University.